Hypercoagulable workup in a community hospital setting: to test or not to test; that is the question - Ashish Gupta; Poras Patel; Raheel Anwar; Diana Villanueva; Viswanath Vasudevan; Elizabeth Guevara (Greater Baltimore Medical Center, 2019)
Background: Thrombophilia tests are often ordered unnecessarily and/or inappropriately, with significant impact on healthcare costs, hospital resources, time, and potential harm to the patient. Objective: To identify the incidence of unnecessary and inappropriate thrombophilia testing in a community hospital setting. Methods: We retrospectively reviewed electronic medical records for patients who underwent inpatient thrombophilia testing at The Brooklyn Hospital Center from 1/1/2018 to 12/31/2018. The indications, and details of the tests, and associated costs were recorded. Results: A total of 62 patients were included (mean age 45.8, 67.7% female). In 57/62 (91.9%) patients, tests were ordered in the acute phase of thrombosis. At the time the tests were ordered, 29/62 (46.8%) patients were on anticoagulation. Positive results were found in 21/62 (53.2%) patients, but was repeated in only 1/21 (4.7%) patient. Results for 51/62 (82%) patients were obtained after discharge. The hematology-oncology service was consulted in 5/62 (8.1%) cases and recommended testing in only 1 (1.6%) patient. Only 1 (1.6%) patient had both an appropriate indication and appropriate testing. Costs for the 273 total tests were $26,400. Conclusion: Thrombophilia tests were often ordered inappropriately and unnecessarily. We recommend testing only for patients with inpatient status under recommendation from the hematology-oncology service.